Evaluating the reality of electronic and remote management - a case study in the General Southern Cement Company - Fouad Youssef Abdel Rahman (Iraqi Journal for Administrative Sciences, 2025)
The study aim to determine the important Electronic Management and Remote Management as modern variable. There is an active role to react qualative change in the managerial and prouductial .Hence the study depend on the descriptive and analytical approach in treating its variables. The study problem has expressed by a group of scientific and theoretical questions. The study has applied on departments and coefficient of southerly sement commonalty company in addition choice community of (30) officials in different levels as: manager coefficient and head of department, Data were collected by using a questionnaire of (17) questions. The questionnaire submitted to descriptive analyzing by mean of the computer to extract the results using the statistical application (SPSS ver-10). The survey reaches to many conclusions ;The most important on , There is no clear tendency to use the Electronic Management Expressions and the Remote Management in research company . but there is great dependence on the traditional way (depentations) to get information and observe (watch) the productivity management processes.